Assessing Stakeholders’ Perception and Adaptation Strategies against Impacts of Climate Change on Agricultural Production (Wheat): A Case Study of Kabul, Afghanistan - Raoufi, Homayoon; Attayee, Sayeed Nabi (Studia Ecologiae et Bioethicae, 2026)
Climate change has serious environmental, economic, and social impacts on the agricultural community in Afghanistan. A combination of many factors, including low socioeconomic situation, poor infrastructure, extreme poverty, rapid population growth, and low adaptive capacity, exerts the agricultural community at extreme vulnerability. Utilizing adaptation strategies by farmers and policymakers plays an important role in minimizing the impacts of climate change. It is important to know how stakeholders perceive the impact of climate change that influences their livelihoods, and the way they use adaptation strategies. This study assessed stakeholders’ perceptions of climate change and vulnerability based on information that was collected from literature and the stakeholders themselves through surveys and interviews. Therefore, the study is primarily focused on Stakeholders’ perception of climate change, effective variables, the impact of climate change on wheat production, and adaptation strategies. Findings revealed that stakeholders had concerns about the negative impact of climate change on crop production. Among the farmers, 90.4% and 72.8% believed that drought and temperature trends had already increased, and only 27.3 % of them thought that rainfall had decreased. The belief of a decrease in crop production due to climatic challenges was recorded by 90.9% and 80% of farmers and agricultural organization workers, respectively. Farmers reported a decrease in crop production of over 46%, and they utilized alternative and tolerant varieties as a means of adapting to the changes and of limiting crop reduction. Agricultural organization workers recommended some strategies including cultivation of adaptive seeds, crop rotation, water resource management, jungle protection, tree planting, increasing public awareness, agriculture machinery, and greenhouse creation, but 33.4 % of them did not provide any suggestions. Stakeholders’ perception and adaptation practices could be improved by the support of organized cooperatives, policy making, training programs, and development of relevant strategies.